The abrasiveness of rock salt when used as a dentifrice on extracted human teeth - Natividad, Pamela Sue A.; Talavera, Jayne Paula P.; Galban, Angelita (Adviser).
In the absence of commercially available dentifrices (toothpastes), alternatives such as salt, soot, sand, and charcoal are used. In the Philippines, rock salt is a common household product that is also used as a dentifrice. This study aimed to determine the abrasiveness of rock salt when used as a dentifrice on extracted human teeth in an in vitro setting. Specifically, this study aimed to determine the changes in weight and thickness of the extracted human teeth after brushing with rock salt and to observe under a zoom microscope the surface appearance of the extracted human teeth before and after brushing with rock salt. This study examines the abrasion that may be caused by rock salt on enamel under controlled experimental conditions simulating manual brushing. Thirty six samples were observed under a zoom microscope and their weight and thickness before brushing were measured and recorded. Same procedures were done after brushing. The teeth were mounted on a customized mounting stage and brushed with rock salt glued to felt wheel for 6 minutes and 25 seconds applying uniform force using a low speed handpiece set at 7000 RPM. The results revealed that after brushing with rock salt for 6 minutes and 25 seconds (equivalent to 8 years and 4 months of manual brushing), the thickness and weight of the teeth decreased by 0.1528 mm and 0.002389 g, respectively. Statistical analysis using paired t-test [P < 0.05] showed that the changes in thickness and weight of the extracted human teeth were statistically significant.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentifrices